Sustentabilidade ambiental : requisito para o cumprimento da função social dos contratos agrários : arrendamento e parceria - Zavascki, Liane Tabarelli (2014)
The purpose of this paper is to examine the hypothesis that the social role of contracts, as regulated in art. 421 of the Brazilian Civil Code (Law # 10406 of 2002), is tied to the fulfillment of sustainability requirements (art. 225, caption, of the 1988 Federal Constitution). Sustainability is understood in this study as a legal value, goal, principle, rule and duty, and carries many interdependent dimensions (economic, social, environmental, legal-political, and ethical). As a result of the vertical and horizontal efficacy of basic rights, the constitutional sustainability principle, which sets forth the right to an ecologically balanced environment, irradiates its effects to Law as a whole, and requires actions that bring it to fruition from both the public authorities and private citizens. On the other hand, on the trail of complying with the constitutional principles and rules, we find that contracts are no longer seen as instruments that exclusively protect the will and conveniences of the parties involved in them, but now play a social, cooperative role between private interests and those of the entire society. Hence, we can say that sustainability conditions contract efficacy and sets limits to private autonomy. However, we understand that such fact does not apply to any and all private contracts, but solely those that generate environmental impacts, such as agrarian contracts. Therefore, environmental sustainability is a requirement for the fulfillment of the social role of agrarian contracts, such as rural lease and partnerships.